Constructing practices of engagement with users and communities: Comparing emergent state-led smart local energy systems. (December 2022) - Soutar, Iain; Devine-Wright, Patrick; Rohse, Melanie; Walker, Chad; Gooding, Luke; Devine-Wright, Hannah; Kay, Imogen
Abstract: Energy transitions require engagement with users, local communities and wider publics in order to be fair, acceptable and, ultimately, successful. Here we focus on the development of decentralised energy systems instigated by central government. Smart Local Energy Systems (SLES), involving low carbon generation, demand sources and smart technologies in a geographically-bounded location, are important but unexplored contexts for public engagement. Drawing on 23 interviews with partner organisations in 12 UK SLES projects, we investigate the targets, methods and rationales of engagement. Partners engage a range of user and community groups around multiple energy system components using a variety of methods, directly and via intermediary organisations. Project size is not a major influence on breadth and intensity of engagement. Project partners rationalise practices with reference to characterisations of users and engagement, and practices are conditioned by a range of factors (e.g. technological boundaries, place, partners involved, and the wider organisational context within which SLES projects take place). We highlight a need for future SLES policy to emphasise engagement as a key facet, institute systematic social learning between SLES projects, and consider how to engage publics beyond the boundaries of individual projects. Highlights: We explore how Smart Local Energy System (SLES) project partners engage publics. Projects engage multiple actors using multiple methods, directly and indirectly. Partners rationalise engagement practices with constructions of users roles. Technologies, place, partners, and wider organisational contexts affect engagement. Future SLES policy could do more to emphasise and shape engagement in SLES projects.